Study of the rare decays of [Formula: see text] and [Formula: see text] into muon pairs from data collected during the LHC Run 1 with the ATLAS detector - Aaboud, M; Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; AbouZeid, O S; Abraham, N L; Abramowicz, H; Abreu, H; Abreu, R; et al. (The European physical journal. C, Particles and fields, 2016)
A study of the decays [Formula: see text] and [Formula: see text] has been performed using data corresponding to an integrated luminosity of 25 fb[Formula: see text] of 7 and 8 TeV proton-proton collisions collected with the ATLAS detector during the LHC Run 1. For the [Formula: see text] dimuon decay, an upper limit on the branching fraction is set at [Formula: see text] at 95 % confidence level. For [Formula: see text], the branching fraction [Formula: see text] is measured. The results are consistent with the Standard Model expectation with a p value of 4.8 %, corresponding to 2.0 standard deviations.